Pengembangan Sumber Daya Manusia Sebagai Faktor Yang Mempengaruhi Produktivitas Kerja Rumah Sakit Sari Asih Karawaci - Arief Hasta Pambudi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Human resource development is a factor that has been empirically proven to have a significant influence on work productivity. This article discusses the results of research on the influence between the two variables. HR as a process in which employees are assisted continuously and planned to acquire or sharpen the abilities necessary to perform various functions related to their current or expected roles in the future. The explanation of HR development also aims to develop employees' abilities as individuals and find and utilize employee potential for the purpose of self-development and/or the company. This study was conducted using a rating scale model questionnaire given to respondents of 57 employees of Sari Asih Karawaci Tangerang Hospital who was the object of the research. The descriptive analysis conducted shows that human resource development is in the effective category while work productivity is in the medium category. The analysis shows that human resource development has a positive and significant influence on work productivity. To increase work productivity, employees must improve their knowledge, skills and motivation so that work productivity can be obtained optimally.